Analysis of initiation of sediment suspension from bed load - Chiew, Yee-Meng (2012)
A theoretical analysis of the initiation of sediment suspension is performed based on the concept of probability of suspension. The proposed condition for the initiation of sediment suspension from the top of the bed-load layer is comparable with most existing empirical relationships for large particle Reynolds numbers. The study shows that a constant Rouse parameter can be used as the critical condition for sediment suspension only for large dimensionless particle diameters. When the probability of suspension is taken to be an infinitesimal value (P = 10^−7), the derived relationship of the Shields parameter and the particle Reynolds number is in good agreement with the updated Shields diagram.